Pengaruh Penggunaan Informasi Akuntansi, Modal Usaha, dan Strategi Pemasaran Terhadap Keberhasilan Usaha (Studi Kasus pada Program Kelompok Usaha Bersama di Kecamatan Jepara) - Halwa Millati; Ali Sofwan (Accounting Study Program, Faculty of Economics and Business, 2022)
The purpose of this study was to determine the effect of using accounting information, venture capital, and marketing strategies on business success (a case study on the Joint Business Group Program in Jepara District). This type of research uses quantitative research methods and uses primary data types by using a questionnaire given to active members of the Joint Business Group (KUBE) program in Jepara District. The total population in this study were 150 people. The sampling technique used purposive sampling, in order to obtain a total sample of 60 respondents through slovin calculations. The statistical analysis phase includes Descriptive Statistics, Validity Test, Reliability Test and Classical Assumption Test. The analysis method uses Multiple Linear Regression Analysis. Based on the results of the study indicate that the use of accounting information has a positive effect on business success, business capital does not have a positive effect on business success and marketing strategy variables do not have a positive effect on business success.